Pemanfaatan Biji Durian menjadi Oleh-Oleh Khas Kampar - Besti Verawati (Indonesian Journal of Cultural and Community Development, 2018)
Durian seeds can used as as valuable flour and not inferior to other flour. This is will increase the economic value and its utilization. Durian seeds contain enough starch, had 8.79% protein, 85% carbohydrates, 980 mg calcium and 1300 mg phosphorus. Durian seed flour can be added in the ingredients of foods such as doughnuts, cakes, semprong, rempeyek, and brownies. That can increase the economic value of durian seed. Family welfare construction group (PKK) of Batu Belah and the Tanjung Bungo village is viable organization empowering women to participate in local development. The activities will be conducted on the increasing knownledge and technology. Furthermore, in this Community there are several development efforts, among other things: 1). Theory to enhance the knowledge about durian seed. 2). Training in the processing of durian seed flour. 3) Increased the motivation of the community. Activities carried out to increase the motivation of the community is the cooking competition in a variety of durian seed flour as kampar special souvenirs, 4) making of a Kampar special food reciepe book as souvenir. 5) marketing strategy. The results of the implementation of the activity that is a. Increased capacity in production system of making Durian Seed Flour; b. an increase in the production of Durian Seed Flour preparations; c. development of marketing strategy.